Princípios constitucionais na gestão pública - Sousa, Luiz Eduardo Monteiro de (Brasil, 2022)
The present work aims to present the importance of the constitucional principles and their application in Public Management, addressing its concept, its application and incorporation in the administration of public managers. The evolution of Brazilian public management was based on the development of three basic management models: patrimonial, bureaucratic and managerial, discovering and implementing the principles that are vital for public management planning, determining the right objectives and then choosing the right means of achieve these objectives.